2008
DOI: 10.1002/dneu.20651
|View full text |Cite
|
Sign up to set email alerts
|

Repeated neonatal separation stress alters the composition of neurochemically characterized interneuron subpopulations in the rodent dentate gyrus and basolateral amygdala

Abstract: Emotional experience during early life has been shown to interfere with the development of excitatory synaptic networks in the prefrontal cortex, hippocampus, and the amygdala of rodents and primates. The aim of the present study was to investigate a developmental "homoeostatic synaptic plasticity" hypothesis and to test whether stress-induced changes of excitatory synaptic composition are counterbalanced by parallel changes of inhibitory synaptic networks. The impact of repeated early separation stress on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 98 publications
2
31
0
2
Order By: Relevance
“…Furthermore, parvalbumin immunoreactive neurons are reduced in the hippocampus of tree shrews after chronic psychosocial stress (Czeh et al, 2005), as well as in Octodon degus after repeated separation stress (Seidel et al, 2008), whereas calbindin immunoreactive neurons were significantly reduced in the CA1 of the hippocampus of mice after inescapable electric foot shocks paradigm (Huang et al, 2010). On these bases, the defects of hippocampal GABAergic markers in SERT À/À animals may contribute to the anxious/depressive phenotype observed in these animals (Olivier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parvalbumin immunoreactive neurons are reduced in the hippocampus of tree shrews after chronic psychosocial stress (Czeh et al, 2005), as well as in Octodon degus after repeated separation stress (Seidel et al, 2008), whereas calbindin immunoreactive neurons were significantly reduced in the CA1 of the hippocampus of mice after inescapable electric foot shocks paradigm (Huang et al, 2010). On these bases, the defects of hippocampal GABAergic markers in SERT À/À animals may contribute to the anxious/depressive phenotype observed in these animals (Olivier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this vein, it is interesting to note that MS decreases DAT levels in the NAcc (Brake et al 2004;Meaney et al 2002). Besides their well-described ability to determine neuronal cell fate (Yu et al 2010) and neuronal morphology in the hippocampus (Fujioka et al 2006;Seidel et al 2008;Sousa et al 2000) and PFC (Bock et al 2005;Cerqueira et al 2007a;Cerqueira et al 2007b;Michelsen et al 2007;Murmu et al 2006), stress (early or in adulthood) and GCs have been found to influence the morphology of neurons in the mesocorticolimbic circuitry. In the above-mentioned study by Leao et al (2007), we observed that GC during late gestation results in a significant reduction in the volume of the NAcc with significant changes in spine density and morphology (Leão, Rodrigues et al, unpublished observations).…”
Section: Linking Els To Daergic Activitymentioning
confidence: 94%
“…Many preclinical studies report effects of MS on the hippocampus (e.g., [1014]), with recent attention turning also to biochemical and physiological effects of MS in the prefrontal cortex (PFC) (1518). The PFC is a relatively late-maturing region (19), is extensively connected with subcortical brain regions, and subserves all higher-order cognitive and emotional functions.…”
mentioning
confidence: 99%